Probing protonation/deprotonation of tyrosine residues in cytochrome ba 3 oxidase from thermus thermophilus by time-resolved step-scan fourier transform infrared spectroscopy - Kolaj-Robin, Olga; Soulimane, Tewfik; Varotsis, Constantinos; Koutsoupakis, Constantinos (My University, 2011)
Elucidating the properties of the heme Fe-Cu B binuclear center and the dynamics of the protein response in cytochrome c oxidase is crucial to understanding not only the dioxygen activation and bond cleavage by the enzyme but also the events related to the release of the produced water molecules. The time-resolved step-scan FTIR difference spectra show the ν 7a(CO) of the protonated form of Tyr residues at 1247 cm -1 and that of the deprotonated form at 1301 cm -1. By monitoring the intensity changes of the 1247 and 1301 cm -1 modes as a function of pH, we measured a pK a of 7.8 for the observed tyrosine. The FTIR spectral changes associated with the tyrosine do not belong to Tyr-237 but are attributed to the highly conserved in heme-copper oxidases Tyr-136 and/or Tyr-133 residue (Koutsoupakis, K., Stavrakis, S., Pinakoulaki, E., Soulimane, T., and Varotsis, C. (2002) J. Biol. Chem. 277, 32860-32866). The oxygenation of CO by the mixed-valence form of the enzyme revealed the formation of the ∼607 nm P (Fe(IV)=O) species in the pH 6-9 range and the return to the oxidized form without the formation of the 580 nm F form. The data indicate that Tyr-237 is not involved in the proton transfer pathway in the oxygenation of CO by the mixed-valence form of the enzyme. The implication of these results with respect to the role of Tyr-136 and Tyr-133 in proton transfer/gating along with heme a 3 ringD propionate-H 2O-ring A propionate-Asp-372 site to the exit/output proton channel (H 2O pool) is discussed
Keywords: Cytochrome C Oxidase; Heme; Thermi Thermophilus